Exploratory miRNA profiling from serum and bone tissue of mice with T1D-induced bone loss - Daamouch, Souad; Diendorfer, Andreas; Hackl, Matthias; Christoffel, Gabriele; Hofbauer, Lorenz C.; Rauner, Martina (Frontiers in Endocrinology, 2024)
Type 1 diabetes (T1D) represents a significant health burden worldwide, with associated complications including bone fragility. Current clinical methods and biomarkers for assessing bone health and predicting fracture risk in T1D are limited and lack accuracy. MicroRNAs (miRNAs) have emerged as potential biomarkers for predicting T1D-induced bone loss, although comprehensive profiling studies are lacking. Previous investigations have indicated a link between dysregulated miRNA expression levels and impaired bone health in T1D. Therefore, in this study, we explored differential miRNA expression levels in serum and bone tissue of mice with T1D-induced bone loss using Next Generation Sequencing (NGS). T1D was induced using streptozotocin in male wild-type mice. Serum and bone tissues were analyzed at 14 weeks of age, following the prior characterization of bone loss in this mouse model. MiRNA profiling was conducted using two-independent NGS analyses and validated through quantitative RT-PCR. NGS profiling identified differential expression of miRNAs in serum and bone tissue of T1D mice compared to controls. The first NGS analysis revealed 24 differentially expressed miRNAs in serum and 13 in bone tissue. Especially, miR-136-3p was consistently downregulated in both serum and bone tissue. However, the second NGS analysis presented a distinct set of dysregulated miRNAs, with miR-206-3p overlapping in both tissues but exhibiting differential expression patterns. Surprisingly, miR-144-5p, miR-19a-3p, and miR-21a-5p displayed contrasting regulatory patterns between NGS and qPCR analyses. Finally, gene network analysis identified associations between dysregulated miRNAs and pathways involved in bone physiology, including TGF-beta, PI3-Akt signaling, and osteoclast differentiation in humans. In conclusion, our study offers initial insights into dysregulated miRNAs associated with T1D-induced bone loss, but also highlights the lack of consistency in the results obtained from miRNA sequencing in different cohorts. Thus, further investigation is needed to better understand the complexities of miRNA analyses before they can be established as reproducible biomarkers for predicting bone health in T1D.